Effects of LPA on the development of sheep in vitro fertilized embryos and attempt to establish sheep embryonic stem cells - Xue-min ZHANG; Xiang-hua HUANG; Jing WANG; Ying XING; Fang LIU; Jin-zhu XIANG; Han-ning WANG; Yong-li YUE; Xue-ling LI (Journal of Integrative Agriculture)
Lysophosphatidic acid (LPA) is a small molecule glycerophospholipid, which regulates multiple downstream signalling pathways through G-protein-coupled receptors to achieve numerous functions on oocyte maturation and embryo development. In this study, sheep in vitro fertilized embryos were applied to investigate the effects of LPA on early embryos development and embryonic stem cell establishment. At first, the maturation medium containing estrus female sheep serum and synthetic oviduct fluid (SOF) were optimized for sheep IVF, and then the effects of LPA were investigated. From 0.1 to 10 μmol L–1, LPA had no significant effect on the cleavage rate (P>0.05), but the maturation rate and blastocyst rate increased dependently with LPA concentration (P<0.05), and the blastocyst morphology was normal. When the LPA concentration was 15 μmol L–1, the maturation rate, cleavage rate and blastocyst rate decreased significantly (P<0.05), and the blastocyst exhibited abnormal morphology and could not develop into high-quality blastocyst. Besides, the exogenous LPA increases the expression of LPAR2, LPAR4, TE-related gene CDX-2 and pluripotency-related gene OCT-4 in sheep early IVF embryos with the raise of LPA concentration from 0.1 to 10 μmol L–1. The expression of LPAR2, LPAR4, CDX-2 and OCT-4 from the LPA-0.1 μmol L–1 to LPA-10 μmol L–1 groups in early embryos were extremely significant (P<0.05), while the expression of these genes significantly decreased in 15 μmol L–1 LPA-treated embryos compared with LPA-10 μmol L–1 group (P<0.05). The inner cell mass in 15 μmol L–1 LPA-treated embryos was also disturbed, and the blastocysts formation was abnormal. Secondly, the sheep IVF blastocysts were applied to establish embryonic stem cells. The results showed that LPA made the blastocyst inoculated cells grow towards TSC-like cells. They enhanced the fluorescence intensity and mRNA abundance of OCT-4 and CDX-2 as the concentration increased from 0 to 10 μmol L–1, while 15 μmol L–1 LPA decreased OCT-4 and CDX-2 expression in the derived cells. The expression of CDX-2 and OCT-4 in the blastocyst inoculated cells of LPA-1 μmol L–1 group and LPA-10 μmol L–1 group extremely significantly increased (P<0.05), but there was significant decrease in LPA-15 μmol L–1 group compared with LPA-10 μmol L–1 group (P<0.05). Meanwhile, the protein expression of LPAR2 and LPAR4 remarkably increased after treatment of LPA at 10 μmol L–1 concentration. This study references the IVF embryo production and embryonic stem cell research of domestic animals.